Research on the Development Dilemma of “Creator Economy” on Social Media Applications among Chinese University Students - Mao Yining (SHS Web of Conferences)
This paper focuses on a blank in the research on the development dilemma of social media creators’ economy mainly targeting current college students, presents interviews with college student content creators, analyzes the reasons, discusses the potential impact of future technological factors and policy support which has important practical significance for the full employment and industry development of future college student creators. In response to the difficulty of achieving equal rewards, the original author’s copyright protection and the platform’s discourse power summarize the ways to solve the development dilemma of creators’ economy in social media applications for college students which the country should strengthen the governance of the internet environment and internet chaos, formulate laws and regulations on the copyright of internet works, regulate the management of internet platforms and the operation of creators and social media platforms should establish a strict verification mechanism to verify the reliability of the content and works published on the platform, enhance the protection of original works and high-quality authors, crackdown on infringers, and prohibit access to the network.